2022
DOI: 10.1177/11786469221111116
|View full text |Cite
|
Sign up to set email alerts
|

Learning Deficits Induced by High-Calorie Feeding in the Rat are Associated With Impaired Brain Kynurenine Pathway Metabolism

Abstract: In addition to be a primary risk factor for type 2 diabetes and cardiovascular disease, obesity is associated with learning disabilities. Here we examined whether a dysregulation of the kynurenine pathway (KP) of tryptophan (Trp) metabolism might underlie the learning deficits exhibited by obese individuals. The KP is initiated by the enzymatic conversion of Trp into kynurenine (KYN) by indoleamine 2,3-dioxygenase (IDO). KYN is further converted to several signaling molecules including quinolinic acid (QA) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Indeed, KA blocks the actions modulated by α7 nicotinic acetylcholine (α7nAChR) and NMDA receptors, whereas excessive activation of NMDA receptors by QA leads to neurotoxicity. In a previous study, we found that obesity‐induced memory deficits are linked to increased concentrations of KA and QA in the brain 34 . Therefore, we sought to determine whether the learning deficits in the offspring of obese parents could be underpinned by impaired production of these two neuroactive compounds.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, KA blocks the actions modulated by α7 nicotinic acetylcholine (α7nAChR) and NMDA receptors, whereas excessive activation of NMDA receptors by QA leads to neurotoxicity. In a previous study, we found that obesity‐induced memory deficits are linked to increased concentrations of KA and QA in the brain 34 . Therefore, we sought to determine whether the learning deficits in the offspring of obese parents could be underpinned by impaired production of these two neuroactive compounds.…”
Section: Resultsmentioning
confidence: 98%
“…In a previous study, we found that obesity-induced memory deficits are linked to increased concentrations of KA and QA in the brain. 34 Therefore, we sought to determine whether the learning deficits in the offspring of obese parents could be T A B L E 1 Statistical differences in the expression levels of genes coding for AMPA and NMDA receptor subunits and markers of glutamate-mediated synaptic plasticity in the brain of adult rats born to obese mothers or sired by obese fathers. underpinned by impaired production of these two neuroactive compounds.…”
Section: Effect Of Maternal and Paternal Obesity On The Metabolism Of...mentioning
confidence: 99%